Resonancias platónicas en la serie de fragmentos 33-36 del Protréptico de Aristóteles - Seggiaro, Claudia (2011)
“Platonic Echoes in the 33-36 fragments of Aristotle’s Protrepticus”. Theaim of this paper is to examine the series of fragments 33-36 of the Protrepticusunder the light of a possible Platonic influence. Our thesis is that, despite the factthat the definition of science as the knowledge of causes and the identificationof these with the principles of reality is an essential conception of Platonism, thefact that we find in the Protrepticus the influence of this conception does not allowus to infer that Aristotle is referring there to the Platonic Ideas or to the idealnumbers defended by his teacher whether it be in his exoteric work or his oralteachings. From our perspective, even though it seems undeniable that, at thetime when he wrote the Protrepticus, Aristotle nourished from some of the mainPlatonic theses, theses which will determine the way in which he understandsreality, it is also undeniable that Aristotle held a critical stand in front of someof the conceptions defended in the nucleus of the Academy.